The use of differential approach for cadets’ special training mark rating - Bondarenko Константин Константинович; Grigorenko Дмитрий Николаевич (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
The mark rating for firefighter’s professional training is developed on the basis of differential approach to the training process. The technique of training on the basis of prognostication the final result is proposed.